Crisis of panatlanticism and «elusive reality» - Antonovich, Ivan I. (Journal of the Belarusian State University. Sociology, 2019)
The article comes to the conclusion, using the analysis of global and geopolitical dynamics, that the dominance of the West, based on the ideology and strategy of panatlantism which covered the period of more than five hundred years of world history, though interrupted by the existence of the alternative world force – the alliance of the socialist states headed by the USSR, has not been restated after falling apart of the Soviet Union. The author comes to the conclusion that the crisis of panatlantism leading to the strengthening of contradictions between its two subjects – United States and European Union contains a serious threat to the world order as the USA and the countries of the EU that are obediently following American lead see the solutions of their problems in the different regions of the world and preparing for the new world war.
Keywords: panatlantism; globalization; world order